Genetic mapping of the N. crassa pho-5 gene - W. K. Versaw; R. L. Metzenberg (Fungal Genetics Reports, 1995)
We have recently cloned and disrupted (by RIP) the N. crassa pho-5 gene which encodes a phosphate-repressible, high-affinity phosphate permease (Versaw 1995 Gene 153:135-139). RFLP analysis indicates that pho-5 maps to Linkage group IV, near pyr-1. We wished to determine the map position of pho-5 more accurately. pho-5 null mutants have no obvious phenotype. Therefore, we constructed parental mapping strains which also contained a null allele of pho-4, a previously isolated high-affinity phosphate permease encoding gene (Mann et al. 1988 Mol. Cell. Biol. 8:1376-1379). pho-5 mutants in a pho-4 background are easily scored by their failure to grow on high pH, low phosphate medium like that used to score nuc-1 and nuc-2 mutants (Metzenberg and Chia 1979 Genetics 93:625-643). Results of the genetic mapping are shown in Table 1. The gene order on Linkage group IV is pyr-1, pho-5, cot-1.